A Formula for Predicting Primary Settlement of Tropical Highly Organic Soil and Peat in the Field - Prativi, Ayu; Mochtar, Noor Endah; Mochtar, Indrasurya B. (Civil Engineering Journal, 2024)
Highly organic soil and peat are problematic soils due to their low bearing capacity and high compressibility. In tropical regions, the presence of woody material in these soils often affects the stress-compression and time-compression curves in load-increment consolidation tests, leading to unusual shapes. Consequently, conventional inorganic soil theory and the Cα/Ccconcept are inadequate for analyzing their compression behavior. As an alternative, the Gibson and Lo model can be used to obtain compression parameters from single-load consolidation tests. However, this method introduces considerable discrepancies when predicting the primary settlement. To address this issue, this paper proposes a formula for predicting the primary settlement in highly organic soil and peat in the field, especially in tropical regions. Samples were collected from several locations in Indonesia. The formula was constructed from the stress-strain relationship during the primary compression stage, obtained from numerous single-load consolidation tests. Long-term field settlement is predicted by combining this empirical equation for primary settlement with the Gibson and Lo model for secondary settlement. The proposed formula was verified using field soil monitoring data, demonstrating reasonable accuracy in predicting the primary settlement of highly organic soil and peat. Doi: 10.28991/CEJ-2024-010-11-03 Full Text: PDF